2007
DOI: 10.1016/j.exger.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary long life spans in fruit-feeding butterflies can provide window on evolution of life span and aging

Abstract: Information on the life span of organisms in the field is essential for elucidating the evolution of life span and aging. We present mark-recapture data (>30,000 marked individuals, >4000 recaptured at least once) on 47 species of fruit-feeding butterflies in a tropical forest in Uganda. The data reveal adult life spans in the field for several species that are significantly longer than previously recorded in Lepidoptera (butterflies and moths). Longevity records for species of which more than 100 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 37 publications
5
58
0
Order By: Relevance
“…The data we collected therefore provide the first direct, empirical support for the commonly held assumption that fruit has higher nitrogen content than nectar (e.g. Fischer et al 2004;Molleman et al 2005aMolleman et al , 2007Beck 2007). Per unit of sugar, we found that the fermenting juice of a wild fruit contained, on average, 39 times more total nitrogenous compounds, 19 times more nonessential amino acids, and 33 times more essential amino acids than nectar.…”
Section: Fruit Has a Higher Nitrogen:carbohydrate Ratio Than Nectarmentioning
confidence: 53%
See 1 more Smart Citation
“…The data we collected therefore provide the first direct, empirical support for the commonly held assumption that fruit has higher nitrogen content than nectar (e.g. Fischer et al 2004;Molleman et al 2005aMolleman et al , 2007Beck 2007). Per unit of sugar, we found that the fermenting juice of a wild fruit contained, on average, 39 times more total nitrogenous compounds, 19 times more nonessential amino acids, and 33 times more essential amino acids than nectar.…”
Section: Fruit Has a Higher Nitrogen:carbohydrate Ratio Than Nectarmentioning
confidence: 53%
“…The dietary switch from nectar to fruit could be related to a more nitrogen-intensive life history. Fruit feeding butterflies are known to have some of the longest lifespans of the Lepidoptera (Molleman et al 2007;Beck 2008); a study of 350 species found that on average, the maximum lifespan of frugivorous species is 2.7 times longer than nectivorous species (Beck and Fiedler 2009). Another long-lived group of butterflies, the heliconiines, acquires amino acids from the external digestion of pollen (Gilbert 1972;O'Brien et al 2003;Eberhard et al 2007).…”
Section: Frugivores Respond More Positively To Amino Acids Than Nectimentioning
confidence: 98%
“…Pijpe et al 2006), field life expectancies in butterflies typically range between 10 and 14 days (e.g. Brakefield & Reitsma 1991;Fischer & Fiedler 2001;but Molleman et al 2007). At the same time, older males showed substantial reductions in two traits likely to be an indicative of condition (cf.…”
Section: Discussionmentioning
confidence: 99%
“…With several important exceptions including studies of a radiocollared marsupial (Austad, 1993), a dipteran species that exhibits extremely high fidelity to mating sites (Bonduriansky & Brassil, 2002, 2005, and fruit-feeding butterflies that restrict their movement to well-circumscribed territories (Molleman et al ., 2006), the majority of investigations on aging rate in the wild are based on large vertebrates, modest numbers, and life table and lifespan data that are either derived from crosssectional data (Deevey, 1947;Caughley, 1977;Promislow, 1991) or augmented with longevity information for captive animals (Carey & Judge, 2000;Kohler et al ., 2006). For studies in which the sample sizes are large and the data collection in the field is longitudinal, the long lifespans of species studied necessitate the construction of costly databases assembled over several decades (Clutton-Brock et al ., 1982;Charmantier et al ., 2006;Nussey et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%